2017
DOI: 10.1186/s13395-017-0121-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Stat3 signaling ameliorates atrophy of the soleus muscles in mice lacking the vitamin D receptor

Abstract: BackgroundAlthough skeletal muscle wasting has long been observed as a clinical outcome of impaired vitamin D signaling, precise molecular mechanisms that mediate the loss of muscle mass in the absence of vitamin D signaling are less clear. To determine the molecular consequences of vitamin D signaling, we analyzed the role of signal transducer and activator of transcription 3 (Stat3) signaling, a known contributor to various muscle wasting pathologies, in skeletal muscles.MethodsWe isolated soleus (slow) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 61 publications
(69 reference statements)
2
24
0
Order By: Relevance
“…39 However, there is a significant minority of patients in whom the fatigue is persistent and disabling, for months or years after likely curative cancer treatment. 44,48,49 The symptom complex of this posttreatment fatigue is very similar to that of chronic fatigue syndrome, including the characteristic fatigue, neurocognitive difficulties, disturbances in sleep-wake cycle and mood, and reduced physical function. 39 Given that the impact of posttreatment fatigue in the adjuvant setting is a key issue affecting cancer survivors, our work has implications for examining the role of interventions, such as graduated exercise [50][51][52] and pharmacological interventions.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…39 However, there is a significant minority of patients in whom the fatigue is persistent and disabling, for months or years after likely curative cancer treatment. 44,48,49 The symptom complex of this posttreatment fatigue is very similar to that of chronic fatigue syndrome, including the characteristic fatigue, neurocognitive difficulties, disturbances in sleep-wake cycle and mood, and reduced physical function. 39 Given that the impact of posttreatment fatigue in the adjuvant setting is a key issue affecting cancer survivors, our work has implications for examining the role of interventions, such as graduated exercise [50][51][52] and pharmacological interventions.…”
Section: Discussionmentioning
confidence: 93%
“…Increased STAT3 tyrosine phosphorylation (tyrosine 705) is a pertinent indicator of canonical STAT3 protein activation, and is representative of an initial upstream inflammatory mediator of muscle wasting . Importantly, STAT3 is a major contributor to muscle atrophy in cancer cachexia and various other muscle pathologies, with blockade of STAT3 signaling leading to amelioration of muscle loss . Alternatively, some studies have demonstrated that oxaliplatin downregulates STAT3 phosphorylation (Tyr705) and activation in cancer cells .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of STAT3 signalling through IL-6 binding to IL-6 receptors has been linked to muscle wasting via stimulation of the myostatin pathway. 33 However, our analyses showed that myostatin (Mstn) gene expression and the activin IIb receptor (Acvr2b) were not affected in response to both short-and long-term exposure to the ICU condition in all investigated muscles ( Figure 5A,B). In addition, ALK4 (Acvr1b) expression was not changed in response to short-and long-term exposure to the ICU condition, except for short-term exposure in the diaphragm where the ALK4 level was induced (P < .05; Figure 5A).…”
Section: Analysis Of Several Pathways That Can Be Involved In Stat3mentioning
confidence: 79%